Analisis Utilisasi Kapasitas Menggunakan Metode Time-Driven Activity Based Costing (TDABC) pada Konveksi Wina - Rikha Diaz Saputri; Faizal Satria Desitama (IPM2KPE, 2023)
Aims to calculate unit costs and resource capacity usage at the Vienna Convection using the Time-Driven Activity Based Costing (TDABC) method. The method used is qualitative with a case study approach. The research results show that Konveksi Vienna's unit cost for size L white is IDR 34,861.17 and color IDR 34,911.17, size XL white is IDR 44,308.14 and color IDR 44,356.92 and size 3L white is IDR 56,042. 43 and color Rp. 56,093.06. At Konveksi Vienna there was a waste of overdeck sewing capacity of 13.63%, overlock sewing and pressure sewing of 35.22%. In conclusion, Vienna convection has a unit cost that is higher than the selling price for size 3L products and the highest capacity waste is in overlock sewing and pressure sewing. Keywords: Unit Cost, Convection, Time-Driven Activity Based Costing (TDABC)